DESIGN OF REAL-TIME OLT MONITORING FOR GPON CONGESTION DETECTION - Marpaung, Hari Jalsa; Ramadhani, Andrew; Harahap, Indra Ramadona (Smart Education, 2025)
Abstract: This research aims to design and implement a web-based Optical Line Terminal (OLT) network monitoring system to detect congestion in real-time on Gigabit Passive Optical Network (GPON) architecture. The main problem in GPON networks is the increase in customer traffic which causes bandwidth bottlenecks and decreases Quality of Service (QoS). The research methodology includes analysis of OLT performance parameters (throughput, utilization, packet loss, latency), design of a system architecture based on SNMP and REST API, development of a monitoring dashboard using a web framework, and testing in an operational network environment. The developed system is able to display PON port status, bandwidth utilization level, and automatic notification when the congestion threshold is exceeded. The test results show that the system can detect an increase in utilization above 80% with a response time of less than 5 seconds. The implementation of this system increases the effectiveness of network monitoring and speeds up the troubleshooting process by administrators. Keywords: Network Monitoring; OLT; GPON; Congestion; Real-Time. Abstrak: Penelitian ini bertujuan merancang dan mengimplementasikan sistem monitoring jaringan Optical Line Terminal (OLT) berbasis web untuk mendeteksi congestion secara real-time pada arsitektur Gigabit Passive Optical Network (GPON). Permasalahan utama pada jaringan GPON adalah meningkatnya trafik pelanggan yang menyebabkan bottleneck bandwidth dan penurunan Quality of Service (QoS). Metodologi penelitian meliputi analisis parameter performa OLT (throughput, utilization, packet loss, latency), perancangan arsitektur sistem berbasis SNMP dan REST API, pengembangan dashboard monitoring menggunakan framework web, serta pengujian pada lingkungan jaringan operasional. Sistem yang dikembangkan mampu menampilkan status port PON, tingkat utilisasi bandwidth, dan notifikasi otomatis ketika threshold congestion terlampaui. Hasil pengujian menunjukkan bahwa sistem dapat mendeteksi kenaikan utilisasi di atas 80% dengan waktu respons kurang dari 5 detik. Implementasi sistem ini meningkatkan efektivitas monitoring jaringan serta mempercepat proses troubleshooting oleh administrator. Kata Kunci: Monitoring Jaringan; OLT; GPON; Congestion; Real-Time.